Digitizing Strategy for MSMEs in Banyumas with a Web-Based Pavlovian Conditioning Approach - Lina Fatimah Lishobrina; Putra Rakhmadani, Diovianto; Puspa Arum, Maliana; Yanyan Ramdhani, Ade (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2026)
This study examines MSME digitalization through a Web-Based Pavlovian Conditioning approach in Cikakak Village by integrating the Technology–Organization–Environment (TOE) and Diffusion of Innovation (DOI) frameworks. The environmental context includes environmental uncertainty and government support, the organizational context focuses on CEO innovativeness, and the technological context emphasizes IT infrastructure. Innovation attributes analyzed under the DOI model include Relative Advantage, Compatibility, Complexity, Trialability, and Observability. Using a quantitative approach, data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with LISREL software. The results show that Relative Advantage, Compatibility, Trialability, Government Support, and Environmental Uncertainty significantly influence website-based digital adoption among MSMEs. These findings indicate that MSME actors prioritize perceived benefits, alignment with existing business processes, and opportunities for experimentation when adopting digital technologies. In contrast, CEO innovativeness, IT infrastructure, complexity, and observability do not significantly affect adoption, suggesting that external support and environmental conditions play a stronger role in early-stage digital ecosystems. Theoretically, this study contributes by integrating TOE and DOI models to provide a more contextual explanation of MSME digital adoption in rural areas, emphasizing the dominant influence of environmental factors over organizational readiness in developing regions.